Training, job satisfaction and workplace performance in Britain: evidence from WERS 2004 - Melanie K. Jones; Richard J. Jones; Paul L. Latreille; Peter J. Sloane (Institute for the Study of Labor (IZA), 2008)
This paper analyses the relationship between training, job satisfaction and workplace performance using the British 2004 Workplace Employee Relations Survey (WERS). Several measures of performance are analysed including absence, quits, financial performance, labour productivity and product quality. While there is clear evidence that training is positively associated with job satisfaction, and job satisfaction in turn is positively associated with most measures of performance, the relationship between training and performance is complex, depending on both the particular measures of training and of performance used in the analysis.
urn:nbn:de:101:1-2008092356
Keywords: J0; 330; Training; job satisfaction; absence; quits; financial performance; labour market; product quality; Betriebliche Weiterbildung; Weiterbildung; Arbeitszufriedenheit; Unternehmensentwicklung; Arbeitsproduktivität; Großbritannien